Drivers of Anaemia Reduction Among Women of Reproductive Age in the Eastern and Upper West Regions of Ghana: A Secondary Data Analysis of the Ghana Demographic and Health Surveys - Tetteh, A; Adanu, R.M.K. (African Journal of Food, Agriculture and Development, 2023)
Anaemia among women of reproductive age (WRA) increases the risk of pregnancy-related morbidity, mortality, and poor pregnancy outcomes. Globally, there is growing interest to reduce anaemia among WRA. In Ghana, anaemia among WRA declined at the national level between 2008 (59%) and 2014 (42%). There were also important declines at the sub-national level. The Eastern region (in the south) and Upper West region (in the north) provide an interesting opportunity to understand the decline. Identifying the drivers of anaemia reduction among WRA in Ghana provides important implementation science evidence for designing effective interventions. This current study examined the drivers of reduced anaemia prevalence in women of reproductive age using data from the Ghana Demographic and Health Surveys for 2008 and 2014. Anaemia was diagnosed as haemoglobin<12.0g/dl. Data were summarized using proportions and 95% confidence intervals. A weighted binary logistic-based multivariate decomposition technique was used to identify the potential drivers of anaemia across surveys for 2003, 2008 and 2014. Sensitivity analysis was carried out to test the robustness of the results of the decomposition analysis using haemoglobin concentration. The results of the decomposition analysis were presented as endowment and coefficient effects. Statistical analysis was carried out using Stata version 15. There was an improvement in access to water and sanitation, health services, family planning, and health insurance across surveys. Drivers of anaemia reduction over time at the national level included wealth index and maternal age, education, use of hormonal contraception and body mass index (BMI). In the Eastern region, the drivers of change were household wealth index, maternal age, hormonal contraceptive use and BMI. The drivers of change in the Upper West region, were household access to water, maternal education and BMI. The findings suggest that multi-level interventions are needed across sectors to further reduce anaemia among WRA.
Research Article
Keywords: Anaemia; Women; Nutrition